2010
DOI: 10.1038/jp.2010.83
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Doppler waveforms in systemic arteries and physiological significance of a patent ductus arteriosus

Abstract: Patent ductus arteriosus in extremely premature babies is associated with major neonatal morbidities, such as necrotizing enterocolitis and intraventricular hemorrhage. This may be attributable, at least in part, to systemic hypoperfusion secondary to ductal steal. A hemodynamically significant ductus arteriosus (HSDA) is known to be associated with altered systemic blood flow and end-organ hypoperfusion. Although descending aorta blood flow profiles may show abnormal diastolic retrograde flow, Doppler studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 45 publications
0
14
1
3
Order By: Relevance
“…The relationship, however, between these echocardiographic markers of ductal steal, actual end-organ tissue oxygen delivery, and adverse outcome remains unclear [19]. Groves et al [13] reported preserved superior vena cava flow but decreased Dao flow in preterm infants with PDA and retrograde diastolic blood flow in the Dao compared with infants with PDA without retrograde diastolic blood flow in the Dao during the first 48 h after birth.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship, however, between these echocardiographic markers of ductal steal, actual end-organ tissue oxygen delivery, and adverse outcome remains unclear [19]. Groves et al [13] reported preserved superior vena cava flow but decreased Dao flow in preterm infants with PDA and retrograde diastolic blood flow in the Dao compared with infants with PDA without retrograde diastolic blood flow in the Dao during the first 48 h after birth.…”
Section: Discussionmentioning
confidence: 99%
“…It has only recently been suggested that a more expectant PDA approach may be superior [2,3] . Although even Doppler waveforms have been used to decide for or against medical/surgical treatment [4,5] , neither echocardiography [6] nor clinical examination can reliably differentiate be-tween hsPDA and the benign variant of a clinically harmless PDA.…”
Section: Introductionmentioning
confidence: 99%
“…1,4 Methods to close or minimize the effects of a clinically significant PDA include conservative management (eg, fluid restriction, diuretics, ventilation strategies), cyclooxygenase inhibitors (eg, indomethacin or ibuprofen), acetaminophen, or surgical ligation. 5,6 Surgical ligation is usually only considered when medical treatment has either failed or was contraindicated. 7 Several investigators have studied PDA ligation and its association with neonatal mortality, short-term morbidity, and neurodevelopmental impairment (NDI) in early childhood.…”
mentioning
confidence: 99%